Changes in Cervical Cytology Results and Human Papillomavirus Types Among Persons Screened for Cervical Cancer, 2007 and 2015–2017. Issue 2 (April 2022) - Lewis, Rayleen M.; Naleway, Allison L.; Klein, Nicola P.; Crane, Bradley; Hsiao, Amber; Aukes, Laurie; Timbol, Julius; Querec, Troy D.; Steinau, Martin; Weinmann, Sheila; Unger, Elizabeth R.; Markowitz, Lauri E.
Abstract : Objectives: Since 2006, the US human papillomavirus (HPV) vaccination program has led to decreases in HPV infections caused by high-risk vaccine-targeted HPV types (HPV 16/18). We assessed differences in high-risk HPV prevalence by cervical cytology result among 20- to 24-year-old persons participating in routine cervical cancer screening in 2015–2017 compared with 2007. Materials and Methods: Residual routine cervical cancer screening specimens were collected from 20- to 24-year-old members of 2 integrated healthcare delivery systems as part of a cross-sectional study and were tested for 37 HPV types. Cytology results and vaccination status (≥1 dose) were extracted from medical records. Cytology categories were normal, atypical squamous cells of undefined significance, low-grade squamous intraepithelial lesions (SIL), or high-grade SIL/atypical squamous cells cannot exclude high-grade SIL. Prevalences of HPV categories (HPV 16/18, HPV 31/33/45/52/58, HPV 35/39/51/56/59/66/68) were estimated by cytology result for 2007 and 2015–2017. Results: Specimens from 2007 ( n = 4046) were from unvaccinated participants; 4574 of 8442 specimens (54.2%) from 2015–2017 were from vaccinated participants. Overall, HPV 16/18 positivity was lower in 2015–2017 compared with 2007 in all groups: high-grade SIL/atypical squamous cells cannot exclude high-grade SIL, 16.0% vs 69.2%; low-grade SIL, 5.4% vs 40.1%; atypical squamous cells of undefined significance, 5.0% vs 25.6%; and normal, 1.3% vs 8.1%. Human papillomavirus 31/33/45/52/58 prevalence was stable for all cytology groups; HPV 35/39/51/56/59/66/68 prevalence increased among low-grade SIL specimens (53.9% to 65.2%) but remained stable in other groups. Conclusions: Prevalence of vaccine-targeted high-risk HPV types 16/18 was dramatically lower in 2015–2017 than 2007 across all cytology result groups while prevalence of other high-risk HPV types was mainly stable, supporting vaccine impact with no evidence of type replacement.